Faktor-faktor yang berhubungan dengan kejadian hipertensi pada usia dewasa wilayah kerja puskesmas pengasinan di kota depok tahun 2022 - Puspa Nujulla; Munaya Fauziah; Andriyani; Ernyasih (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Hypertension is still one of the most common diseases in Indonesia. Hypertension is a condition in which a person experiences blood pressure above the standard limit so that it will cause illness or even death. Indonesia contributes to a lot of people who suffer from hypertension. Based on a doctor's diagnosis in the population aged 18 years (Riskesdas, 2018), the incidence of hypertension in 2013 was 25.8%, then increased in 2018, which was 34.1%. This is an analytic study with a cross-sectional research design to see the relationship between family history, gender, physical activity patterns, high salt intake, and obesity on the incidence of hypertension in adulthood. The sample used purposive sampling with a sample of 130 respondents, then analyzed by univariate and bivariate using Chi-square test and non-parametric test, Mann Whitney U test. From 130 respondents, 72 (55.4%) respondents had hypertension and 58 (44.6%) respondents did not. The results of the bivariate test using the Chi-Square test and non-parametric test with = 0.005 were found; there is no significant relationship between family history and the incidence of hypertension (p-value = 0.176), there is no significant relationship between gender and the incidence of hypertension (p-value = 0.928), there is no significant relationship between the pattern of physical activity and the incidence of hypertension (p-value = 0.780), there is a significant relationship between the consumption of high-salt foods and the incidence of hypertension (p-value = 0.001), there is a significant relationship between obesity and the incidence of hypertension (p-value = 0.026). Factors related to the incidence of hypertension in adulthood are high consumption of salt (p value = 0.001) and obesity (p value = 0.026). Do regular blood pressure checks, reduce excessive salt consumption, and do physical activity for at least 30 minutes to keep the body from becoming obese.